Pain Mirrors: Neural Correlates of Observing Self or Others’ Facial Expressions of Pain - Benuzzi, Francesca; Lui, Fausta; Ardizzi, Martina; Ambrosecchia, Marianna; Ballotta, Daniela; Righi, Sara; Pagnoni, Giuseppe; Gallese, Vittorio; Porro, Carlo Adolfo (Frontiers in Psychology, 2018)
Facial expressions of pain are able to elicit empathy and adaptive behavioral responses in the observer. An influential theory posits that empathy relies on an affective mirror mechanism, according to which emotion recognition relies upon the internal simulation of motor and interoceptive states triggered by emotional stimuli. We tested this hypothesis comparing representations of self or others’ expressions of pain in nineteen young healthy female volunteers by means of functional magnetic resonance imaging (fMRI). We hypothesized that one’s own facial expressions are more likely to elicit the internal simulation of emotions, being more strictly related to self. Video-clips of the facial expressions of each volunteer receiving either painful or non-painful mechanical stimulations to their right hand dorsum were recorded and used as stimuli in a 2x2 (Self/Other; Pain/No-Pain) within-subject design. During each trial, a 2-s video clip was presented, displaying either the subject’s own neutral or painful facial expressions (Self No-Pain, SNP; Self Pain, SP), or the expressions of other unfamiliar volunteers (Others’ No-Pain, ONP; Others’ Pain, OP), displaying a comparable emotional intensity. Participants were asked to indicate whether each video displayed a pain expression. fMRI signals were higher while viewing Pain than No-Pain stimuli in a large bilateral array of cortical areas including middle and superior temporal, supramarginal, superior mesial and inferior frontal (IFG) gyri, anterior insula (AI), anterior cingulate (ACC) and anterior mid-cingulate (aMCC) cortex, as well as right fusiform gyrus. Bilateral activations were also detected in thalamus and basal ganglia. The Self vs Other contrast showed signal changes in ACC and aMCC, IFG, AI and parietal cortex. A significant interaction between Self and Pain [(SPvsSNP)>(OPvsONP)] was found in a pre-defined region of aMCC known to be also active during noxious stimulation. These findings demonstrate that the observation of one’s own and others’ facial expressions share a largely common neural network, but self-related stimuli induce generally higher activations. In line with our hypothesis, selectively greater activity for self pain-related stimuli was found in aMCC, a medial-wall region critical for pain perception and recognition.